Negotiating Social Inclusion: The Catholic Church in Australia and the Public Sphere - Lynch, Andrew P. (2016)
This paper argues that for religion, social inclusion is not certain once gained, but needs to be constantly renegotiated in response to continued challenges, even for mainstream religious organisations such as the Catholic Church. The paper will analyse the Catholic Church’s involvement in the Australian public sphere, and after a brief overview of the history of Catholicism’s struggle for equal status in Australia, will consider its response to recent challenges to maintain its position of inclusion and relevance in Australian society. This will include an examination of its handling of sexual abuse allegations brought forward by the Royal Commission into Institutional Responses to Child Sexual Abuse, and its attempts to promote its vision of ethics and morals in the face of calls for marriage equality and other social issues in a society of greater religious diversity.